REMEDIASI MISKONSEPSI MENGGUNAKAN MODEL REASONING AND PROBLEM SOLVING PADA MATERI SUHU DAN KALOR DI SMP - Noviyanti, Noviyanti; Sitompul, Stepanus Sahala; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research was conducted to obtain the influence of the use of a model reasoning and the problem solving of experimentation and a simulation of misconception fall in the number of students. Methods used in this research is experimental design quasi non-equivalent design goes next to the control group. Sample be conducted by way of intact group (group intact). Data collection was carried out by giving shaped double test choice reason closed consisting of 9. Based on the research done, the average of the percentage of misconception, the number of students on class experiment of 38,09 % and in a class of 27,78 %. Then, with the significance of 5 % obtained x hitung = 4,99 and x tabel = 5,99 , this shows that there is no significant influence model reasoning and the use of solving the problem of experiment and the use of models and simulation of reasoning problem solving. One of the effectiveness of from the study is 56,79 for the class experimentation and 41,90 for the class simulation calculated use of DQM (Decreasing Quantity Misconception). The outcome of the findings from the study expected can be used as assessments to help the teacher's physics overcome their mistakes students in overcoming the misconception of students in particular to the matter heat engine and change form substance. Keywords: remediation, misconception, reasoning and problem solving model, experiment, simulation.